2014
DOI: 10.1371/journal.pone.0084484
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation versus Hepatic Resection for Small Hepatocellular Carcinomas: A Meta-Analysis of Randomized and Nonrandomized Controlled Trials

Abstract: ObjectivesTo evaluate the efficacy and safety of radiofrequency ablation (RFA) versus hepatic resection (HR) for early hepatocellular carcinoma (HCC) meeting the Milan criteria.MethodsA meta-analysis was conducted, and PubMed, Web of Science, the Cochrane Library, CBM, CNKI and VIP databases were systematically searched through November 2012 for randomized and nonrandomized controlled trials (RCTs and NRCTs). The Cochrane Collaboration's tool and modified MINORS score were applied to assess the quality of RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 41 publications
(58 reference statements)
3
85
2
3
Order By: Relevance
“…A recent meta‐analysis28, including three RCTs11, 12, 13 and several retrospective studies14, 15, 16 comparing RFA with surgical resection, concluded that RFA was comparable to surgical resection in terms of survival, with lower complication rates but higher recurrence rates, consistent with the present results. A study29 comparing RFA with surgical resection for solitary small HCC using a propensity score model showed that surgical resection provided better OS and RFS than RFA.…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta‐analysis28, including three RCTs11, 12, 13 and several retrospective studies14, 15, 16 comparing RFA with surgical resection, concluded that RFA was comparable to surgical resection in terms of survival, with lower complication rates but higher recurrence rates, consistent with the present results. A study29 comparing RFA with surgical resection for solitary small HCC using a propensity score model showed that surgical resection provided better OS and RFS than RFA.…”
Section: Discussionsupporting
confidence: 88%
“…This technique is being applied in several Asian countries with good results [43,44] . Several randomized controlled trials compared the efficacy of RFA with that of resection in Asian patients with HCC meeting the Milan criteria [45,46] . Pooled data demonstrated no significant differences in overall survival or recurrence-free survival between the treatments at 1 and 3 years.…”
Section: Interventional Therapiesmentioning
confidence: 99%
“…Pooled data demonstrated no significant differences in overall survival or recurrence-free survival between the treatments at 1 and 3 years. The 5-year overall survival [relative risk (RR), RR = 0.72, 95% confidence interval (CI): 0.60-0.88] and recurrence-free survival (RR = 0.56, 95%CI: 0.40-0.78) rates were higher in the resection group [46] ; however, the 5-year data were provided by only one study, which advocated surgery. Complication rates were lower and hospitalization period shorter in patients who received RFA rather than resection [46] .…”
Section: Interventional Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early and timely diagnosis, and surgical resection or interventional therapy could help significantly in improving the patient's survival rate, and prolong their survival time (8). Diagnosis of small HCC is acquired solely by imaging as patients with small HCC have no clinical signs.…”
Section: Introductionmentioning
confidence: 99%